Luxury products and distribution through internet platforms from the European Competition Law (ECJ C-230/16, Coty Case) - Arroyo Aparicio, Alicia (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This study analyzes EJC Case Law referring to the selective distribution agreements of luxury cosmetic products and the compatibility of the restriction of sales of these products through online platforms, under the perspective of Antitrust European Law. In particular, the Judgment of December 6, 2017, Coty Germany GbmH c. Parfümerie Akzente GmbH is considered, but also it is important to take into account the evolution from Metro Case to Coty. Three issues are highlighted: selective distribution and Competition Law, compatibility of the prohibition to market on internet platforms - “amazon.de” was the specific platform in Coty- Case and the interconnection with the Trademarks Law.